Sex specific function of epithelial STAT3 signaling in pathogenesis of K-ras mutant lung cancer. Issue 1 (December 2018) - Caetano, Mauricio; Hassane, Maya; Van, Hieu; Bugarin, Emmanuel; Cumpian, Amber; McDowell, Christina; Cavazos, Carolina; Zhang, Huiyuan; Deng, Shanshan; Diao, Lixia; Wang, Jing; Evans, Scott; et al.
Abstract Lung adenocarcinomas (LUADs) with mutations in theK-ras oncogene display dismal prognosis. Proinflammatory and immunomodulatory events that drive development ofK-ras mutant LUAD are poorly understood. Here, we develop a lung epithelial specificK-ras mutant/Stat3 conditional knockout (LR/Stat3 Δ/Δ ) mouse model. EpithelialStat3 deletion results in intriguing sex-associated discrepancies;K-ras mutant tumors are decreased in female LR/Stat3 Δ/Δ mice whereas tumor burdens are increased in males. RNA-sequencing and tumor microenvironment (TME) analysis demonstrate increased anti-tumor immune responses followingStat3 deletion in females and, conversely, elevated pro-tumor immune pathways in males. While IL-6 blockade in male LR/Stat3 Δ/Δ mice reduces lung tumorigenesis, inhibition of estrogen receptor signaling in female mice augmentsK-ras mutant oncogenesis and reprograms lung TME toward a pro-tumor phenotype. Our data underscore a critical sex-specific role for epithelialStat3 signaling inK-ras mutant LUAD, thus paving the way for developing personalized (e.g. sex-based) immunotherapeutic strategies for this fatal disease. Proinflammatory and immunomodulatory events that drive development ofK-ras mutant lung adenocarcinoma (LUAD) are poorly understood. Here they develop a lung epithelial specificK-ras mutant/Stat3 conditional knockout mouse model and show a sex-specific role for epithelialStat3 signaling inK-ras -mutant LUAD.